The Integrated Analysis Identifies Three Critical Genes as Novel Diagnostic Biomarkers Involved in Immune Infiltration in Atherosclerosis - Ye, Zhen; Wang, Xiao-kang; Lv, Yun-hui; Wang, Xin; Cui, Yong-chun (Frontiers in Immunology, 2022)
Atherosclerosis (AS), a chronic inflammatory disease of the blood vessels, is the primary cause of cardiovascular disease, which is the leading cause of death worldwide. The purpose of this study was to identify possible diagnostic markers for AS and to determine their correlation with the infiltration of immune cells in AS. 10 serum samples from AS patients and 10 healthy samples were collected. The original gene expression profiles GSE43292 and GSE57691 were downloaded from GEO database. The LASSO regression model and SVM-RFE analysis were carried out for the identification of candidate markers. The diagnostic values of the identified biomarker were determine by the use of ROC assays. The compositional patterns of the 22 types of immune cell fraction in AS were estimated using CIBERSORT. RT-PCR was further performed to determine the expression of the critical genes. In this study, we identified 17 differentially expressed genes (DEGs) in AS samples. The identified DEGs were mainly involved in non-small cell lung carcinoma, pulmonary fibrosis, polycystic ovary syndrome, glucose intolerance and T-cell leukemia. FHL5, IBSP and SCRG1 were identified the diagnostic genes in AS. The expression of SCRG1 and FHL5 was distinctly down-regulated in AS samples and the expression of IBSP was distinctly up-regulated in AS samples, which was further confirmed using our cohort by RT-PCR. Moreover, immune assays revealed that FHL5, IBSP and SCRG1 were associated with several immune cells, such as T cells CD8, B cells naïve, Macrophages M0, T cells CD4 memory activated and NK cells activated. Overall, it is possible that future investigations into the occurrence and molecular mechanisms of AS will benefit from the use of the genes FHL5, IBSP, and SCRG1 as diagnostic markers for the condition.